Sodium-glucose co-transporter-2 inhibitors and the risk of major arrhythmias: a meta-analysis of the cardiovascular and renal outcome trials. (14th October 2021) - Boulmpou, A; Patoulias, D; Teperikidis, E; Papadopoulos, C E; Sarafidis, P; Doumas, M; Fragakis, N; Pagourelias, E; Vassilikos, V
Abstract: Background: Type 2 diabetes mellitus is closely associated with cardiovascular disease and evidence already exists on its arrhythmogenic action. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are a unique class of oral antidiabetic medications which recently attracted attention for reducing the total risk of major adverse cardiovascular events in a series of recent, large placebo-controlled randomized clinical trials (RCTs). Dapagliflozin and empagliflozin additionally seem to improve survival and outcomes in patients with heart failure with reduced ejection fraction (HFrEF), irrespective of the presence of diabetes mellitus. Whether antidiabetic treatment with sodium-glucose co-transporter inhibitors could reduce the arrhythmic burden in diabetic patients still is to be clarified. Purpose: The purpose of the present meta-analysis was to report the impact of SGLT2i on the risk for several types of cardiac arrhythmias, pooling data from all relevant cardiovascular and renal outcome, placebo-controlled, RCTs, comparing SGLT2i to placebo. Methods: We searched PubMed for all available cardiovascular and renal outcome RCTs utilizing SGLT2i, along with grey literature sources. We sought to determine the risk of the following arrhythmias/cardiac disorders with the use of SGLT2i versus placebo: atrial fibrillation, atrial flutter, supraventricular tachycardia, ventricular tachycardia, ventricular fibrillation, ventricular extrasystoles, sinus bradycardia, sinus node dysfunction, second degree atrioventricular block, complete atrioventricular block. Results: We extracted relevant data from 8 trials (5 dedicated cardiovascular outcome trials, 2 dedicated renal outcome trials, 1 trial enrolling patients with HFrEF), pooling data in a total of 55, 966 patients. SGLT-2i treatment compared to placebo produced a significant reduction in the risk of atrial fibrillation equal to 21% (RR=0.79, 95% CI: 0.67–0.93, I 2 =0%) (Figure 1). A non-significant reduction in the risk of atrial flutter equal to 9% (RR=0.91, 95% CI: 0.64–1.29, I 2 =0%) was also observed with SGLT2i (Figure 2). No significant effect on the rest major arrhythmias was observed. Conclusions: Antidiabetic therapy with SGLT2i seems to hold a significant impact on antiarrhythmic burden in type 2 diabetes mellitus, reducing the risk of atrial fibrillation development. FUNDunding Acknowledgement: Type of funding sources: None.